The Importance of Movement and Operation as Preventive Conservation Strategies for Heritage Machinery. Issue 2 (3rd April 2017) - Wain, Alison
Abstract : Machines are designed to move, and that movement is fundamental to their significance, both in their service lives and in subsequent lives as heritage. Movement, and particularly operation, contributes to maintaining the intangible heritage of how to operate and maintain machines, as well as the affective and sensory experiences associated with their operation. Movement also helps to preserve the physical fabric of machines by facilitating actions such as the circulation of lubricants and rotation of pressure points. Movement can, however, also have negative effects on the preservation of original physical material through wear and component failure, and many museums find the cost and expertise requirements for moving heritage machines daunting. These challenges mean that many machines are stored and displayed as static items, despite the consequent loss of intangible heritage, the development of stress and corrosion problems, and the lack of opportunities for audiences to develop personal and emotional connections with the machines. This paper argues that partial or full movement strategies should be considered to be a normal and important aspect of preventive care of heritage machinery, to ensure that the tangible and intangible significance of that machinery is appropriately preserved. The paper draws on research into the conservation of contemporary kinetic and time-based art, which deals with similar challenges.